THE EFFECT OF USING CNC SIMULATOR ON MOTIVATION AND MASTERY OF CNC MACHINING TECHNIQUE COMPETENCIES OF VOCATIONAL HIGH SCHOOL STUDENTS - Hasanuddin; Sunardi; Z. Kiru, Chandra (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2024)
This research aims to determine: (1) The effect of using the CNC Simulator on student learning motivation in the CNC Machining Engineering subject at SMKN 1 Paguyaman. (2) The influence of using the CNC Simulator on Students' Competency Mastery in the CNC Machining Engineering subject at SMKN 1 Paguyaman. The research method used in this research is Pre-Experimental. The research design used in this research is One Group Pre-Test - Post-Test Design combined with One-Shot Case Study. The research subjects were students of class XI Mechanical Engineering at SMKN 1 Paguyaman with a total of 15 students. Research data collection techniques use questionnaires and tests. Normality test using Shapiro-Wilk. Hypothesis testing uses Paired Sample t-test and One Sample t-test. The results of the research show: (1) There is an influence of using the CNC Simulator on Student Learning Motivation in the CNC Machining Engineering subject at SMKN 1 Paguyaman, based on the results of the t-test Learning Motivation tcount ≤ ttable, namely -28.221 ≤ 1.761 with a significance value of 0.000 < 0, 05. (2) There is an influence of using the CNC Simulator on Student Competency Mastery in the CNC Machining Engineering subject at SMKN 1 Paguyaman, based on the results of the Student Competency t-test tcount ≥ ttable, namely 4.513 ≥ 1.761 with a significance value of 0.000 < 0.05.